Is it time to ban oxytocin for poor labour progress?. Issue 6 (June 2019) - Walker, Kate F.; Bugg, George
Abstract: Oxytocin causes myometrial contractions and prostaglandin release. It is commonly used as an intervention for women in established labour with slow progress. However recent large randomised trials of oxytocin for this indication have shown no difference in caesarean section rates associated with its use. This may be due to inadequate doses of oxytocin and small randomised studies have suggested high dose oxytocin may indeed reduce caesarean delivery. The results of a high quality large randomised trial of high versus low dose oxytocin for women with slow progress are keenly awaited. There is no evidence to support the concept of turning the oxytocin off once contractions have been established, although this certainly merits further investigation. Recent evidence of contemporary labour patterns indicate that our whole concept of slow progress in labour is fundamentally flawed.